Helicobacter pylori infection and functional dyspepsia in adolescence - Pereira, Carlos (2015)
Introduction: Studies confirm that Helicobacter pylori (H. pylori) infection may be a predisposing factor for gastric pathology later in life. This study consisted in determining the prevalence of H. pylori present in the stomach and functional dyspepsia in sample of Portuguese adolescents. Participants and methods: A sample of 437 adolescents aged 12 to 19 years old, attending a public school in Sátão, Portugal, was enrolled in this cross sectional study. A self-administered questionnaire focusing socio-demographic variables, social and daily habits and gastric-related pathologies was filled out by all participants in this study. The self-reported form for children and adolescents of the Rome III Diagnostic Questionnaire was also applied in order to assess functional dyspepsia. The adolescents were screened for H. pylori infection using the Urease Breath Test (UBT) that consists in the exhalation of carbon dioxide in samples before and after swallowing urea labeled with non radioactive carbon-13. Prevalence was expressed in proportions and compared by the chi-square test. Crude odds ratio (OR) with 95% confidence intervals (CI) were used. Results: The prevalence of gastric H. pylori was 35.9%. Functional dyspepsia was present in 22.4% of the sample and was associated with age (≤ 15years OR=2.25, 95%CI=1.17-4.33), residential area (rural OR=1.98, 95%CI=1.05-4.35) and family history of gastric disease (OR=3.39, 95%CI=1.17-9.87). After adjustment by multivariate logistic regression for socio-demographic variables and family history of gastric disease, the results demonstrate no association between H. pylori infection and functional dyspepsia (OR=1.08 95%CI=0.8-1.3). Conclusions: We found a high prevalence of H. pylori infection and functional dyspepsia among adolescents, suggesting that gastric pathology continues to be an important public health issue. This study provides important baseline measurements for future preventive measures